Ultra-soft flat cable with anti-electromagnetic interference capability and preparation process thereof
By using insulating materials of PET, GO and mica powder, ultra-soft wires with three-layer structure of insulating material-conductor-insulating material are formed, which solves the problems of cumbersome and high cost of soft wire processes in the prior art, and realizes anti-electromagnetic interference and cost reduction effects.
Patent Information
- Application Number
- CN202411609422.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The existing soft cables are complicated and complicated when isolating signal magnetic wave interference, resulting in high production costs.
The insulating material including PET, GO and mica powder is used to form a super soft line with a three-layer structure of insulating material-conductor-insulating material through hot pressing and injection molding.
It has achieved improvement in anti-electromagnetic interference capability, while reducing production costs and simplifying processes.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ultra-soft flat cables, and in particular to an ultra-soft flat cable with anti-electromagnetic interference capability and a preparation process thereof. Background Art
[0002] Soft flat cable, also known as flexible flat cable (FFC), can arbitrarily select the number and spacing of wires, which is convenient for connection, reducing the size of electronic products, reducing production costs and improving production efficiency. Due to its own advantages such as arbitrary bending and high signal transmission, it is widely used in mobile parts and motherboards, PCB boards, and small electrical equipment as data transmission cables.
[0003] Chinese patent CN117174364A discloses an FFC cable containing anti-electromagnetic interference PET material and a preparation process. The FFC cable mainly includes a PET material layer, a rubber layer, and a flat conductor layer.
[0004] In order to achieve the purpose of isolating signal magnetic wave interference, most of the flexible flat cables are covered with conductive cloth. The production process of such flexible flat cables is cumbersome and complicated, and the production cost is high. Therefore, we propose an ultra-soft flat cable with anti-electromagnetic interference ability and its preparation process. Summary of the invention
[0005] The object of the present invention is to provide an ultra-soft flat cable with anti-electromagnetic interference capability and a preparation process thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solution: an ultra-soft flat cable with anti-electromagnetic interference capability, comprising a conductor and an insulating material, wherein the insulating material is located on the outer surface of the conductor.
[0007] Furthermore, the insulating material comprises components: PET (polyethylene terephthalate), GO (graphene oxide) and filler;
[0008] The filler is mica powder.
[0009] A preparation process of an ultra-soft flat cable with anti-electromagnetic interference capability comprises the following steps:
[0010] S1: Select copper foil as the conductor, lay insulating material on its upper and lower surfaces respectively to form a three-layer structure of insulating material-conductor-insulating material, hot press, cool and solidify to form insulating material covering the outer surface of the conductor, and obtain a flexible flat cable;
[0011] S2: Cut the flexible flat cable, test its conductivity, and package it after it passes the test.
[0012] In S1, the copper foil thickness is 0.5 mm and is sourced from Kunshan Weibo Adhesive Products Co., Ltd.;
[0013] Furthermore, in S1, the process conditions of hot pressing are: temperature 150-170° C., duration 30-40 min;
[0014] The process conditions for cooling and curing are: temperature 25-35°C, time 1-2h.
[0015] Furthermore, the insulating material is obtained by mixing GO / PET composite material and filler, co-extruding and injection molding.
[0016] Furthermore, the mass ratio of GO / PET composite material to filler is 100:(1-3).
[0017] Furthermore, the process conditions of co-extrusion are: temperature 220-250° C., rotation speed 300-500 r / min.
[0018] Furthermore, the process conditions of injection molding are: injection molding speed 50-150 mm / s, injection molding time 5-10 s, and temperature 280-300°C.
[0019] Furthermore, the GO / PET composite material is obtained by compounding modified PET and GO;
[0020] The modified PET is prepared from isosorbide, 1,4-cyclohexanedimethanol and PET through a direct esterification-melt polycondensation method.
[0021] Furthermore, the GO / PET composite material is prepared by the following process:
[0022] Mix isosorbide, 1,4-cyclohexanedimethanol and PET, and under the protection of nitrogen atmosphere, heat to 230-240°C, pressure 0.2-0.4MPa, and react for 1-3h; after the reaction, evacuate the system, control the temperature at 275-285°C, pressure 75-95Pa, keep warm for 6-8h, then discharge and pelletize to obtain modified PET;
[0023] The modified PET and GO are mixed at high speed and melt-extruded to obtain a GO / PET composite material.
[0024] Furthermore, the mass ratio of modified PET and GO is (95-98):(2-5).
[0025] Furthermore, the process conditions for high-speed mixing are: rotation speed 1350-1450 r / min, duration 5-15 min, temperature 70-80°C.
[0026] Furthermore, the process conditions of melt extrusion are: temperature 265-275° C., rotation speed 40-50 r / min.
[0027] Further, the mass ratio of isosorbide, 1,4-cyclohexanedimethanol, and PET is 1:(1-3):(2-6);
[0028] Isosorbide CAS number: 652-67-5, purity: 99%, from Shandong Hui'an Chemical Co., Ltd.;
[0029] 1,4-Cyclohexanedimethanol CAS number: 105-08-8, purity: 99%, from Shandong Shangwei Chemical Import and Export Co., Ltd.;
[0030] PET, brand: RE5329, comes from Dongguan Xinshengli Plastic New Material Technology Co., Ltd.
[0031] Furthermore, the GO is modified, and the specific process is as follows:
[0032] The silane coupling agent and 50% ethanol by mass fraction are mixed in a mass ratio of 1:10, and hydrolyzed at 50-60° C. for 30-40 min to obtain a silane coupling agent hydrolyzate;
[0033] The silane coupling agent hydrolyzate is sprayed on the surface of GO and dried to obtain modified GO.
[0034] Furthermore, the mass ratio of silane coupling agent to GO is 1:(0.5-0.7).
[0035] Furthermore, the drying process conditions are: temperature 65-85°C, time 3.5-4.5h.
[0036] Furthermore, the silane coupling agent is KH570, CAS No.: 2530-85-0, from Shandong Huachen New Materials Co., Ltd.;
[0037] GO: particle size 2000 mesh, purity: 99%, sourced from Lingshou County Jianshi Mineral Powder Factory.
[0038] In the above technical scheme, isosorbide has a special rigid structure. Introducing it into the molecular chain of PET can improve the rigidity of the molecular chain, reduce the free volume of the matrix, reduce the gaps between the molecular chains, block the penetration of small molecules, and improve the heat resistance of PET; 1,4-cyclohexanedimethanol is a cyclic aliphatic diol with a symmetrical structure and good thermal stability. The cyclohexyl group in the molecular structure has a certain rigidity. Introducing it into the molecular chain of PET further improves the heat resistance and impact strength of PET; GO not only has a two-dimensional layered structure, but also contains a large number of polar groups on the surface. The polar groups can interact with the composite material as active sites, further enhancing the overall performance of the composite material, but GO has a strong specific surface energy and is easy to agglomerate together. Therefore, GO is modified with a silane coupling agent without producing by-products and improving the interface compatibility between GO and the composite material.
[0039] Furthermore, the filler is mica powder, which is modified by a silane coupling agent before use. The specific process is as follows:
[0040] The mica powder was mixed with deionized water, ultrasonically dispersed for 30 minutes, a silane coupling agent was added, the temperature was raised to 50-60°C, and the mixture was stirred for reaction for 1.5-2.0 hours. After the reaction was completed, the mixture was washed and filtered for 2-4 times, and vacuum dried to constant weight to obtain a modified filler.
[0041] Furthermore, the mass ratio of mica powder, deionized water, and silane coupling agent is 1:(4-7):(0.1-0.15);
[0042] Mica powder particle size: 10-1250 mesh, SiO2 content: 45.2%, Al2O3 content: 38.5%, sourced from Lingshou County Yikun Mineral Products Co., Ltd.
[0043] The silane coupling agent is KH570, which comes from Shandong Huachen New Materials Co., Ltd.
[0044] Furthermore, the stirring speed is 400-500 r / min.
[0045] Furthermore, the process conditions of vacuum drying are: temperature 90-100° C., time 3-5 h.
[0046] In the above technical scheme, mica as an inorganic filler can be used to improve the insulation performance, thermal stability and high temperature resistance of the material, but its surface polarity is large and it is easy to agglomerate, so it is modified using a silane coupling agent; the silanol group of the silane coupling agent forms a chemical bond with the hydroxyl group on the surface of the mica, and the organic functional group can form a chemical bond or physical entanglement with the organic matrix, thereby improving the compatibility and dispersibility of mica in the organic matrix. The addition of modified mica improves the thermal stability and high temperature resistance of the insulating material.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] 1. Taking advantage of the special rigid structure of isosorbide, it is introduced into the molecular chain of PET, which improves the rigidity of the molecular chain, reduces the free volume of the matrix, reduces the gaps between the molecular chains, blocks the penetration of small molecules, and improves the heat resistance of PET. 1,4-Cyclohexanedimethanol is a cyclic aliphatic diol with a symmetrical structure and good thermal stability. The cyclohexyl group in the molecular structure has a certain rigidity. Introducing it into the molecular chain of PET further improves the heat resistance and impact strength of PET. GO not only has a two-dimensional layered structure, but also contains a large number of polar groups on the surface. The polar groups can interact with the composite material as active sites, further enhancing the overall performance of the composite material. However, GO has a strong specific surface energy and is easy to agglomerate. Therefore, GO is modified with a silane coupling agent without producing by-products and improving the interface compatibility between GO and the composite material.
[0049] 2. Mica can be used as an inorganic filler to improve the insulation performance, thermal stability and high temperature resistance of materials, but its surface polarity is large and it is easy to agglomerate. Mica is modified by silane coupling agent so that the silanol groups of the coupling agent form chemical bonds with the hydroxyl groups on the surface of mica, and the organic functional groups form chemical bonds or physical entanglements with the organic matrix, which improves the compatibility and dispersibility of mica in the organic matrix. The addition of modified mica improves the thermal stability and high temperature resistance of the insulating material. DETAILED DESCRIPTION
[0050] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] In the following specific implementations,
[0052] The copper foil thickness is 0.5 mm and comes from Kunshan Weibo Adhesive Products Co., Ltd.;
[0053] Isosorbide CAS number: 652-67-5, purity: 99%, from Shandong Hui'an Chemical Co., Ltd.;
[0054] 1,4-Cyclohexanedimethanol CAS number: 105-08-8, purity: 99%, from Shandong Shangwei Chemical Import and Export Co., Ltd.;
[0055] PET, brand: RE5329, from Dongguan Xinshengli Plastic New Material Technology Co., Ltd.;
[0056] The silane coupling agent is KH570, CAS No.: 2530-85-0, from Shandong Huachen New Materials Co., Ltd.
[0057] GO: particle size 2000 mesh, purity: 99%, sourced from Jianshi Mineral Powder Factory, Lingshou County;
[0058] The filler is mica powder with a particle size of 10-1250 mesh, SiO2 content: 45.2%, Al2O3 content: 38.5%, and is sourced from Lingshou County Yikun Mineral Products Co., Ltd.
[0059] Embodiment 1: A process for preparing an ultra-soft flat cable with anti-electromagnetic interference capability, comprising the following steps:
[0060] (1) Preparation of GO / PET composites:
[0061] Mix isosorbide, 1,4-cyclohexanedimethanol and PET, and heat to 230°C and 0.2MPa under nitrogen atmosphere for 1h. After the reaction, evacuate the system and control the temperature at 275°C and 75Pa. Keep the temperature for 6h before discharging and pelletizing to obtain modified PET. The mass ratio of isosorbide, 1,4-cyclohexanedimethanol and PET is 1:1:2.
[0062] The silane coupling agent and 50% ethanol by mass fraction are mixed in a mass ratio of 1:10, and hydrolyzed at 50° C. for 30 min to obtain a silane coupling agent hydrolyzate;
[0063] The silane coupling agent hydrolyzate is sprayed on the surface of GO and dried to obtain modified GO; the mass ratio of silane coupling agent to GO is 1:0.7;
[0064] The modified PET and modified GO were mixed at high speed and melt extruded to obtain a GO / PET composite material; the process conditions for high-speed mixing of the modified PET and modified GO with a mass ratio of 95:5 were: speed 1350r / min, duration 5min, temperature 70°C; the process conditions for melt extrusion were: temperature 265°C, speed 40r / min;
[0065] (2) Preparation of modified filler:
[0066] The mica powder was mixed with deionized water, ultrasonically dispersed for 30 minutes, silane coupling agent was added, the temperature was raised to 50°C, stirred for reaction for 1.5 hours, washed and filtered twice after the reaction, and vacuum dried to constant weight to obtain a modified filler; the mass ratio of mica powder, deionized water, and silane coupling agent was 1:4:0.1; the stirring speed was 400r / min; the process conditions of vacuum drying were: temperature 90°C, time 3 hours;
[0067] (3) Preparation of insulating materials:
[0068] The GO / PET composite material and the modified filler were mixed, co-extruded, and injection molded to obtain an insulating material; the mass ratio of the GO / PET composite material and the modified filler was 100:1; the process conditions of the co-extrusion were: temperature 220°C, rotation speed 300r / min; the process conditions of the injection molding were: injection molding speed: 50mm / s, injection molding time: 5s, temperature: 280°C;
[0069] (4) Preparation of ultra-soft flat cable:
[0070] S1: Select copper foil as the conductor, lay insulating material on its upper and lower surfaces respectively to form a three-layer structure of insulating material-conductor-insulating material, hot press, cool and solidify, form insulating material covering the outer surface of the conductor, and obtain a flexible flat cable; S2: Cut the flexible flat cable, test its conductivity, and package it after it passes the test; the process conditions of hot pressing in S1 are: temperature 150℃, duration 30min; the process conditions of cooling and solidification are: temperature 25℃, duration 1h.
[0071] Embodiment 2: A process for preparing an ultra-soft flat cable with anti-electromagnetic interference capability, comprising the following steps:
[0072] (1) Preparation of GO / PET composites:
[0073] Mix isosorbide, 1,4-cyclohexanedimethanol and PET, and heat to 235°C and pressure 0.3MPa under nitrogen atmosphere protection, and react for 2h; after the reaction, evacuate the system, control the temperature at 280°C and pressure 85Pa, and keep the temperature for 7h before discharging and pelletizing to obtain modified PET; the mass ratio of isosorbide, 1,4-cyclohexanedimethanol and PET is 1:2:4;
[0074] The silane coupling agent and 50% ethanol by mass fraction were mixed in a mass ratio of 1:10, and hydrolyzed at 55° C. for 35 min to obtain a silane coupling agent hydrolyzate;
[0075] The silane coupling agent hydrolyzate is sprayed on the surface of GO and dried to obtain modified GO; the mass ratio of silane coupling agent to GO is 1:0.6;
[0076] The modified PET and modified GO were mixed at high speed and melt extruded to obtain a GO / PET composite material; the mass ratio of modified PET to modified GO was 96:4; the process conditions for high-speed mixing were: speed 1400r / min, duration 10min, temperature 75°C; the process conditions for melt extrusion were: temperature 270°C, speed 45r / min;
[0077] (2) Preparation of modified filler:
[0078] The mica powder was mixed with deionized water, ultrasonically dispersed for 30 minutes, silane coupling agent was added, the temperature was raised to 55°C, stirred for reaction for 1.8 hours, washed and filtered 3 times after the reaction, and vacuum dried to constant weight to obtain a modified filler; the mass ratio of mica powder, deionized water, and silane coupling agent was 1:5:0.13; the stirring speed was 450r / min; the process conditions of vacuum drying were: temperature 95°C, time 4h;
[0079] (3) Preparation of insulating materials:
[0080] The GO / PET composite material and the modified filler were mixed, co-extruded, and injection molded to obtain an insulating material; the mass ratio of the GO / PET composite material and the modified filler was 100:2; the process conditions of the co-extrusion were: temperature 235°C, rotation speed 400r / min; the process conditions of the injection molding were: injection molding speed: 100mm / s, injection molding time: 7s, temperature: 290°C;
[0081] (4) Preparation of ultra-soft flat cable:
[0082] S1: Select copper foil as the conductor, lay insulating material on its upper and lower surfaces respectively to form a three-layer structure of insulating material-conductor-insulating material, hot press, cool and solidify, form insulating material covering the outer surface of the conductor, and obtain a flexible flat cable; S2: Cut the flexible flat cable, test its conductivity, and package it after it passes the test; the process conditions of hot pressing in S1 are: temperature 160℃, time 35min; the process conditions of cooling and solidification are: temperature 30℃, time 1.5h.
[0083] Embodiment 3: A process for preparing an ultra-soft flat cable with anti-electromagnetic interference capability, comprising the following steps:
[0084] (1) Preparation of GO / PET composites:
[0085] Mix isosorbide, 1,4-cyclohexanedimethanol and PET, and under the protection of nitrogen atmosphere, heat to 240℃, pressure 0.4MPa, and react for 3h; after the reaction, evacuate, control the system temperature at 285℃, pressure 95Pa, keep warm for 8h, then discharge and pelletize to obtain modified PET; the mass ratio of isosorbide, 1,4-cyclohexanedimethanol and PET is 1:3:6;
[0086] The silane coupling agent and 50% ethanol by mass fraction were mixed in a mass ratio of 1:10, and hydrolyzed at 60° C. for 40 min to obtain a silane coupling agent hydrolyzate;
[0087] The silane coupling agent hydrolyzate is sprayed on the surface of GO and dried to obtain modified GO; the mass ratio of silane coupling agent to GO is 1:0.5;
[0088] The modified PET and modified GO were mixed at high speed and melt extruded to obtain a GO / PET composite material; the mass ratio of modified PET to modified GO was 98:2; the process conditions for high-speed mixing were: speed 1450r / min, duration 15min, temperature 80°C; the process conditions for melt extrusion were: temperature 275°C, speed 50r / min;
[0089] (2) Preparation of modified filler:
[0090] The mica powder was mixed with deionized water, ultrasonically dispersed for 30 minutes, silane coupling agent was added, the temperature was raised to 60°C, stirred and reacted for 2.0 hours, washed and filtered 4 times after the reaction, and vacuum dried to constant weight to obtain a modified filler; the mass ratio of mica powder, deionized water, and silane coupling agent was 1:7:0.15; the stirring speed was 500r / min; the process conditions of vacuum drying were: temperature 100°C, time 5 hours;
[0091] (3) Preparation of insulating materials:
[0092] The GO / PET composite material and the modified filler were mixed, co-extruded, and injection molded to obtain an insulating material; the mass ratio of the GO / PET composite material and the modified filler was 100:3; the process conditions of the co-extrusion were: temperature 250°C, speed 500r / min; the process conditions of the injection molding were: injection molding speed: 150mm / s, injection molding time: 10s, temperature: 300°C;
[0093] (4) Preparation of ultra-soft flat cable:
[0094] S1: Select copper foil as the conductor, lay insulating material on its upper and lower surfaces respectively to form a three-layer structure of insulating material-conductor-insulating material, hot press, cool and solidify, form insulating material covering the outer surface of the conductor, and obtain a flexible flat cable; S2: Cut the flexible flat cable, test its conductivity, and package it after it passes the test; the process conditions of hot pressing in S1 are: temperature 170℃, duration 40min; the process conditions of cooling and solidification are: temperature 35℃, duration 2h.
[0095] Comparative Example 1: Compared with Example 1, the filler is not modified during the preparation of the insulating material. A preparation process of an ultra-soft flat cable with anti-electromagnetic interference capability includes the following steps:
[0096] (1) Preparation of GO / PET composite material: isosorbide, 1,4-cyclohexanedimethanol and PET were mixed, heated to 230°C and pressure of 0.2 MPa under nitrogen atmosphere, and reacted for 1 h; after the reaction, vacuum was evacuated, and the system temperature was controlled at 275°C and pressure of 75 Pa. After 6 h of heat preservation, the material was discharged and pelletized to obtain modified PET; the mass ratio of isosorbide, 1,4-cyclohexanedimethanol and PET was 1:1:2;
[0097] The silane coupling agent and 50% ethanol by mass fraction are mixed in a mass ratio of 1:10, and hydrolyzed at 50° C. for 30 min to obtain a silane coupling agent hydrolyzate;
[0098] The silane coupling agent hydrolyzate is sprayed on the surface of GO and dried to obtain modified GO; the mass ratio of silane coupling agent to GO is 1:0.7;
[0099] The modified PET and modified GO were mixed at high speed and melt extruded to obtain a GO / PET composite material; the process conditions for high-speed mixing of the modified PET and modified GO with a mass ratio of 95:5 were: speed 1350r / min, duration 5min, temperature 70°C; the process conditions for melt extrusion were: temperature 265°C, speed 40r / min;
[0100] (2) Preparation of insulating materials:
[0101] The GO / PET composite material and filler are mixed, co-extruded, and injection molded to obtain an insulating material; the mass ratio of the GO / PET composite material to the filler is 100:1; the process conditions of co-extrusion are: temperature 220°C, speed 300r / min; the process conditions of injection molding are: injection molding speed: 50mm / s, injection molding time: 5s, temperature: 280°C;
[0102] (3) Preparation of ultra-soft flat cable:
[0103] S1: Select copper foil as the conductor, lay insulating material on its upper and lower surfaces respectively to form a three-layer structure of insulating material-conductor-insulating material, hot press, cool and solidify, form insulating material covering the outer surface of the conductor, and obtain a flexible flat cable; S2: Cut the flexible flat cable, test its conductivity, and package it after it passes the test; the process conditions of hot pressing in S1 are: temperature 150℃, duration 30min; the process conditions of cooling and solidification are: temperature 25℃, duration 1h.
[0104] Comparative Example 2: Taking Example 1 as a comparison, GO and PET are not modified during the preparation of the insulating material. A preparation process of an ultra-soft flat cable with anti-electromagnetic interference capability includes the following steps:
[0105] (1) Preparation of GO / PET composites:
[0106] PET and GO were mixed at high speed and melt extruded to obtain GO / PET composite materials; the mass ratio of PET to GO was 95:5; the process conditions for high-speed mixing were: speed 1350r / min, duration 5min, temperature 70°C; the process conditions for melt extrusion were: temperature 265°C, speed 40r / min;
[0107] (2) Preparation of modified filler: the same as in Example 1;
[0108] (3) Preparation of insulating material: the same as in Example 1;
[0109] (4) Preparation of ultra-soft flat cable: same as in Example 1.
[0110] Comparative Example 3: Compared with Example 1, modified GO is not added during the preparation of the insulating material. A preparation process of an ultra-soft flat cable with anti-electromagnetic interference capability includes the following steps:
[0111] (1) Preparation of modified filler: the same as in Example 1;
[0112] (2) Preparation of insulating materials:
[0113] PET and modified filler are mixed, co-extruded, and injection molded to obtain insulating material; the mass ratio of PET to modified filler is 100:1; the process conditions of co-extrusion are: temperature 220°C, speed 300r / min; the process conditions of injection molding are: injection molding speed: 50mm / s, injection molding time: 5s, temperature: 280°C;
[0114] (3) Preparation of ultra-soft flat cable: same as in Example 1.
[0115] experiment:
[0116] The ultra-soft flat cables obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were used to prepare samples, and their performances were tested and the test results were recorded:
[0117] Tensile performance test: According to GB / T 1040-2006, the test speed is set to 10mm / min;
[0118] Impact performance test: According to GB / T 1043-2008, the notch specimen width is 10mm and the length is 80mm.
[0119] Heat deformation temperature test: According to GB / T 1634-2004, the test load is 0.45MPa.
[0120] Tensile strength / MPa <![CDATA[Notched impact strength / (J·m -1 )]]> Heat deformation temperature / ℃ Example 1 60.23 93.21 93.3 Example 2 61.70 94.87 94.5 Example 3 62.91 96.03 95.1 Comparative Example 1 59.35 88.96 92.7 Comparative Example 2 58.73 87.37 91.9 Comparative Example 3 57.99 86.95 91
[0121] According to the data in the above table, we can clearly draw the following conclusions:
[0122] The ultra-soft flat cables obtained in Examples 1-3 are compared with the ultra-soft flat cables obtained in Comparative Examples 1-3. The test results show that:
[0123] Compared with comparative example 1, the ultra-soft flat cables obtained in examples 1 to 3 have better tensile strength, notched impact strength and higher thermal deformation temperature, which fully demonstrates that the insulating material provided in the present invention achieves the improvement of the tensile strength, notched impact strength and thermal deformation temperature of the ultra-soft flat cables.
[0124] Compared with Example 1, in Comparative Example 1, the filler is not modified when preparing the insulating material, chemical bonding cannot be formed, and the high temperature resistance is reduced; in Comparative Example 2, GO and PET are not modified when preparing the insulating material, and the heat resistance and impact strength are reduced; in Comparative Example 3, modified GO is not added when preparing the insulating material, and the tensile strength of the insulating material is significantly reduced; it can be seen that the setting of the process and the materials used in this application can promote the improvement of the tensile strength, notched impact strength and heat deformation temperature of the prepared insulating material.
[0125] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A process for preparing an ultra-soft flat cable with anti-electromagnetic interference capability, characterized in that: The following steps are involved: S1: Select copper foil as the conductor, lay insulating material on its upper and lower surfaces respectively to form a three-layer structure of insulating material-conductor-insulating material, hot press, cool and solidify to form insulating material covering the outer surface of the conductor, and obtain a flexible flat cable; S2: Cut the flexible flat cable, test its conductivity, and package it after it passes the test.
2. The process for preparing an ultra-soft flat cable with anti-electromagnetic interference capability according to claim 1, characterized in that: The insulating material in S1 is obtained by mixing GO / PET composite material and filler, co-extruding and injection molding.
3. The process for preparing an ultra-soft flat cable with anti-electromagnetic interference capability according to claim 2, characterized in that: The GO / PET composite material is prepared by the following process: Mix isosorbide, 1,4-cyclohexanedimethanol and PET, and under the protection of nitrogen atmosphere, heat to 230-240°C, pressure 0.2-0.4MPa, and react for 1-3h; after the reaction, evacuate the system, control the temperature at 275-285°C, pressure 75-95Pa, keep warm for 6-8h, then discharge and pelletize to obtain modified PET; The modified PET and GO are mixed at high speed and melt-extruded to obtain a GO / PET composite material.
4. The process for preparing an ultra-soft flat cable with anti-electromagnetic interference capability according to claim 2, characterized in that: The filler is mica powder, which is modified by a silane coupling agent before use. The specific process is as follows: The mica powder was mixed with deionized water, ultrasonically dispersed for 30 minutes, a silane coupling agent was added, the temperature was raised to 50-60°C, and the mixture was stirred for reaction for 1.5-2.0 hours. After the reaction was completed, the mixture was washed and filtered for 2-4 times, and vacuum dried to constant weight to obtain a modified filler.
5. The process for preparing the ultra-soft flat cable with anti-electromagnetic interference capability according to claim 3, characterized in that: The GO is modified, and the specific process is as follows: The silane coupling agent and 50% ethanol by mass fraction are mixed in a mass ratio of 1:10, and hydrolyzed at 50-60° C. for 30-40 min to obtain a silane coupling agent hydrolyzate; The silane coupling agent hydrolyzate is sprayed on the surface of GO and dried to obtain modified GO.
6. The process for preparing an ultra-soft flat cable with anti-electromagnetic interference capability according to claim 2, characterized in that: The process conditions of co-extrusion are: temperature 220-250°C, rotation speed 300-500r / min.
7. The process for preparing an ultra-soft flat cable with anti-electromagnetic interference capability according to claim 1, characterized in that: In S1, the process conditions of hot pressing are: temperature 150-170° C., time 30-40 min; the process conditions of cooling and curing are: temperature 25-35° C., time 1-2 h.
8. The process for preparing an ultra-soft flat cable with anti-electromagnetic interference capability according to claim 2, characterized in that: The mass ratio of GO / PET composite material to filler is 100:(1-3).
9. The process for preparing an ultra-soft flat cable with anti-electromagnetic interference capability according to claim 3, characterized in that: The mass ratio of isosorbide, 1,4-cyclohexanedimethanol and PET is 1:(1-3):(2-6).
10. An ultra-soft flat cable with anti-electromagnetic interference capability, characterized in that: The invention is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
FFC (Flexible Flat Cable) containing anti-electromagnetic interference PET (Polyethylene Terephthalate) material and preparation process
CN117174364A